PERFORMANCE OF POLYMER GROUTS MADE FROM WASTES FOR PERMEABLE RIGID PAVEMENT CONNECTIONS - Lau, Zong Ying; Lee, Shyue Leong; Abdul Mannan, Mohammad; Slavcheva, Galina Stanislavovna; Oucif, Chahmi (Journal of Civil Engineering, Science and Technology, 2022)
This research developed polymer grouts made from wastes such as fly ash, palm oil fuel ash, and silica fume. The selected polymer grouts served as an interlocking key between the StormPav covers and as a grout to seal the gaps between the interlocking keys and StormPav covers. Based on compressive strength and workability of the polymer grouts, mix ratio of resin to fly ash = 1:1.00 was chosen as the grout, while mix ratio of resin to fly ash = 1:1.50 was used to form an interlocking key. Mix ratios of resin to fly ash = 1:1.00 and resin to fly ash = 1:1.50 had a compressive strength of 98.90 MPa and 81.70 MPa, respectively, and flexural strength of 53.00 MPa and 61.90 MPa. Moreover, increasing the fly ash content in polymer grout decreased the water absorption and volume of permeable voids. In terms of shear strength, the mix ratio of resin to fly ash = 1:1.00 performed well as grout, with a determined shear strength of 3.98 MPa. Even after 25 days of exposure to the high concentration of sodium hydroxide, sulphuric acid, sodium chloride, and magnesium sulphate, the determined shear strength met the minimum shear strength requirement of 1.38 MPa as stated by the Iowa Department of Transportation. Therefore, it can be concluded that both selected mix ratios were suitable for use as grout and interlocking key due to their good physical and mechanical properties.